Gene Expression Analysis Indicates Divergent Mechanisms in DEN-Induced Carcinogenesis in Wild Type and Bid-Deficient Livers. - Changshun Yu; Shengmin Yan; Bilon Khambu; Xiaoyun Chen; Zheng Dong; Jianhua Luo; George K Michalopoulos; Shangwei Wu; Xiao-Ming Yin (PLoS ONE)
Bid is a Bcl-2 family protein. In addition to its pro-apoptosis function, Bid can also promote cell proliferation, maintain S phase checkpoint, and facilitate inflammasome activation. Bid plays important roles in tissue injury and regeneration, hematopoietic homeostasis, and tumorigenesis. Bid participates in hepatic carcinogenesis but the mechanism is not fully understood. Deletion of Bid resulted in diminished tumor burden and delayed tumor progression in a liver cancer model. In order to better understand the Bid-regulated events during hepatic carcinogenesis we performed gene expression analysis in wild type and bid-deficient mice treated with a hepatic carcinogen, diethylnitrosamine. We found that deletion of Bid caused significantly fewer alterations in gene expression in terms of the number of genes affected and the number of pathways affected. In addition, the expression profiles were remarkably different. In the wild type mice, there was a significant increase in the expression of growth regulation-related and immune/inflammation response-related genes, and a significant decrease in the expression of metabolism-related genes, both of which were diminished in bid-deficient livers. These data suggest that Bid could promote hepatic carcinogenesis via growth control and inflammation-mediated events.